Intra-octahedral proton transfer in bulk orthorhombic perovskite barium cerate - Jeong, Yong-Chan; Kim, Dae-Hee; Kim, Byung-Kook; Kim, Yeong-Cheol (ELSEVIER, 2012)
Intra-octahedral proton transfer in bulk orthorhombic perovskite barium cerate was investigated in order to understand the proton transfer mechanism using density functional theory. Since Ce-centered octahedrons tilt in the orthorhombic perovskite structure to accommodate the tensile strain between Ba and O ions, the Ce-O-Ce unit is bent. A proton attached to an O ion can transfer intra-octahedrally to a neighboring O ion in the structure. An energy barrier of 1.06 eV is required as the bent Ce-O-Ce unit is straightened and bent in the opposite direction during proton transfer. When the bent Ce-O-Ce unit rotates without being straightened during proton transfer, a much lower energy barrier of 0.26 eV is required. The energy barrier for proton transfer by rotating the bent Ce-O-Ce unit increases to 0.45 eV, when the proton transfers near a Y ion that is substituted for a Zr ion as a dopant. Therefore, the proton transfers by rotating the bent Ce-O-Ce unit in bulk orthorhombic barium cerate, resulting in better agreement with experimentally measured energy barriers (0.5-0.54 eV). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: INITIO MOLECULAR-DYNAMICS; TOTAL-ENERGY CALCULATIONS; IONIC-RADII; CONDUCTION; HYDROGEN; ZIRCONATE; DEFECT